The Crosstalks Between Jasmonic Acid and Other Plant Hormone Signaling Highlight the Involvement of Jasmonic Acid as a Core Component in Plant Response to Biotic and Abiotic Stresses - Yang, Jing; Duan, Guihua; Li, Chunqin; Liu, Lin; Han, Guangyu; Zhang, Yaling; Wang, Changmi (Frontiers in Plant Science, 2019)
Plant hormones play central roles in the complex processes of plant growth, development and response to biotic and abiotic stresses. On one hand, plant hormones may allocate limited resources to most serious stresses, on the other hand, the crosstalks among multiple plant hormone signalings regulate the balance between plant growth and defense during the processes. Jasmonic acid (JA) and other plant hormones are commonly involved in regulating plant growth, development and stress responses. Many studies have reported the mechanism of crosstalks between JA and other plant hormones in plant growth and stress response. Based on these studies, this paper mainly reviews that the crosstalks between JA and other plant hormone signalings regulate the balance between plant growth and defense. The suppressor protein JASMONATE-ZIM DOMAIN PROTEIN (JAZ) as the key component in the crosstalks is also highlighted in the review. We conclude that JA interacts with other hormone signaling pathways (such as auxin, ethylene (ET), abscisic acid (ABA), salicylic acid (SA), brassinosteroids (BRs) and gibberellin (GA)) to regulate plant growth, abiotic stress tolerance, and defense against hemibiotrophic pathogens such as Magnaporthe oryzae and Pseudomonas syringae. Notably, JA acts as core signal to regulate plant response to environmental stresses in phytohormones signaling network.